Financial Derivative Instruments and Their Applications in Islamic Banking and Finance: Fundamentals, Structures, and Pricing Mechanisms - Uluyol, Burhan; Uluyol, Burhan (Borsa Istanbul Anonim Sirketi, 2024)
There is ongoing debate regarding the permissibility of financial derivatives in Islamic banking and finance. While traditional derivative products are rejected by most Islamic schools of thought as permissible tools for risk management, there have been developments in Shariah-compliant structured products to address this need. Therefore, the objectives of the study are twofold: i) to examine the permissibility and acceptability of financial derivatives within Islamic economics and finance, and ii) to investigate their structures and pricing models. This study finds that these instruments can be utilised for risk management purposes while adhering to the principles of wealth protection in Islam. It is also crucial to prohibit elements such as speculation, gambling, and gharar while using financial derivatives in Islamic banking and Finance. As a contribution to the study, this research aims to incorporate traditional option pricing models into Shariah-compliant derivatives, which has been a topic that has been scarcely explored in previous studies.
Keywords: Financial derivatives; Binomial option pricing model (BOPM); The black-scholes pricing model (BSOPM); Shariah-compliant derivatives; Islamic finance